Roles of formal institutions and social capital in innovation activities: a cross-country analysis - Weng, Chang Lee; Siong, Hook Law (Routledge, 2017)
This paper investigates the roles of formal institutions and social capital in countries’ innovation activities. The sample consists of 62 developed and developing countries, using the ordinary least squares robust standard error estimations, instrumental variable (IV) estimators, and quantile regression. The empirical results indicate that formal institutions and social capital complement one another in influencing countries’ innovations level. In terms of the relative importance of both in promoting innovation activities, the social capital has greater role compared to formal institutions. Furthermore, the empirical result suggests that innovation level tends to be higher in countries with higher social capital. We also use the quantile regression to estimate whether the relationship among formal institutions, social capital, and innovation differs at different points in the conditional distribution of innovation. The results demonstrate that formal institutions yield a significant positive impact only after exceeding in 50th quantile, whereas social capital do so at lower 10th quantile. Therefore, in addition to a policy focus on improving the formal institutions, countries with a low level of innovation should enrich social capital in their promotion of innovation activity.